Towards a Herstory of Art Curriculum? - Triviño-Cabrera, Laura; Chaves Guerrero, Elisa sabel; Lucas Palacios, Laura (Clio. History and History Teaching, 2019)
The aim of this article is to explore the possibility of a Herstory of Art Curriculum, understanding the visibility of biographies and art works of women. On the one hand, this study tries to deconstruct the hidden curriculum, using a postmodern curriculum proposal that incorporates the her / stories of Art. On the other hand, this article developpes a quantiative analysis of the presence or absence of women artists in the History of Art Curriculum subjects of different Spanish legislations until it results in a study based on the critical analysis of the feminist discourse of the curriculum of Fundamentals of Art I and II of High School.